A vast temporal continuum for sensory processing arises from a nontopographic cellular multilevel gradient - Kathrin D. Wicke; Nikolaos Kladisios; Kathrin Kattler-Lackes; Felix Felmy (Proceedings of the National Academy of Sciences, 2026)
Classification of neurons into discrete populations aids the comprehension of neuronal function. However, such simplifications do not fully reflect the complexity and gradual nature of sensory stimuli and internal representations. Therefore, heterogeneous neuronal populations might be more adequate to process and represent neuronal function compared to discrete populations. Using patch-seq recordings, we identify a heterogeneous cell population in the auditory brainstem that forms an extensive functional continuum through molecular, biophysical, and synaptic gradients. Through the interaction of this multilevel gradient, this population spans nearly the full range of known membrane time constants forming a temporal filter bank. This temporal filter bank matches the range of relevant frequencies of environmental sound transients. This arrangement processes early cross-frequency integration producing a holistic information of environmental sound transients known to be relevant during speech and pitch detection. Thus, the presence of a functionally continuous neuronal population relates to the complexity of stimulus information.